Sudden Cardiac Arrest in a Patient With COVID-19 as a Result of Severe Hyperkalemia After Administration of Succinylcholine Chloride for Reintubation. A Case Report - Putowski, Mateusz; Drygalski, Tomasz; Morajda, Andrzej; Woroń, Jarosław; Sanak, Tomasz; Wordliczek, Jerzy (Frontiers in Medicine, 2022)
Abstract Background: We present a case study of a man with COVID 19 who developed cardiac arrest as a result of hyperkalemia following administration of chlororsuccinylcholine during endotracheal intubation. Case Summary: A patient with a severe course of COVID-19, hospitalized in the Intensive Care Unit, underwent reintubation on day 16. The applied scheme was rapid sequence induction and intubation with administration of chlororsuccinylcholine. Immediately after intubation, there was a sudden cardiac arrest due to hyperkalemia (cK + 10.2 meq / L). Treatment was initiated as per guidelines, which resulted in a return to spontaneous circulation after 6 minutes. Conclusions: Chlorsucynylcholine may cause life-threatening hyperkalemia. We recommend using rocuronium as a neuromuscular blocking agent in critically ill COVID-19 patients due to its more optimal safety profile.